The role of increased sunshine in shaping air temperature rise in Kraków (1951–2020) - Marsz, Andrzej A.; Matuszko, Dorota; Styszyńska, Anna (Quaestiones Geographicae, 2025)
Since the late 1980s, air temperature in Kraków (southern Poland) has increased by ~2.2–2.3°C compared to the 1951–1988 average. Over the same period, a significant increase in sunshine duration (SD) (by about 500 hr) has been observed relative to the 1951–1988 baseline. This pattern of temperature change in Kraków is representative of trends observed across Poland. The aim of this study is to determine the impact of SD on the increase in air temperature in Kraków. The analysis indicates that the strong rise in SD has resulted from changes in cloud structure since the late 1980s. During this period, the frequency of frontal stratiform clouds (As, Ns, St) decreased, while the occurrence of Sc, Cu, and Cb clouds increased. These shifts in cloud structure, driven by changes in mid-tropospheric macro-circulation, have led to an increase in SD. An analysis of the combined influence of three factors – annual SD, the NAO PC DJFM index (Hurrell), and radiative forcing (∆F) – on annual temperature trends between 1951 and 2020 shows that the variability of these factors explains 67.3% of the variance in annual air temperature (R = 0.83, p << 0.001), fully accounting for the observed temperature increase within the margin of estimation error. Of this, SD variability explains 58% of the variance, NAO index variability accounts for 7.7%, and ∆F variability contributes 3.6%. These findings indicate that the primary driver of air temperature increase in Kraków is the rise in SD (solar radiation influx) rather than radiative forcing (∆F).